ANALYSIS OF THE LEVEL OF FISHERMEN'S COMPLIANCE IN COASTAL ENVIRONMENTAL MANAGEMENT BASED ON LOCAL WISDOM (Case Study: The Role of Panglima Laot in North Aceh Regency) - Eva Wardah; Setia Budi; Nopri Yanto (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Coastal resource management based on local wisdom regulates environmental conservation customs for the sustainability of coastal resources in Aceh Province. As direct users of marine resources, fishermen have a key role in maintaining the sustainability of coastal ecosystems. The level of compliance of fishermen in the utilization of coastal resources is very important. Specifically, this study aims to identify problems in coastal area management related to the implementation of customary law in North Aceh Regency and to analyze the level of compliance of fishermen in terms of maintaining the coastal environment based on customary law. This study uses a survey method where the determination of the location is determined purposively (intentionally) in North Aceh Regency. Primary data were obtained from fishermen through structured interviews (questionnaires) involving 80 fishermen while secondary data were obtained from various agencies related to this study. Data were analyzed qualitatively with Likert scale measurements. The results of the study showed that the problems that occurred in the coastal area of ​​North Aceh Regency were dominated by the use of environmentally unfriendly fishing gear, lack of supporting facilities and infrastructure for the activities of the Panglima Laot institution, and low human resources of the Panglima Laot institution apparatus. Based on the analysis of the level of compliance of fishing communities in maintaining the coastal environment, the following are in order: 1) Prohibition on bombing and anesthetizing fish. (2) Not violating the no-go days at sea. (3) Not damaging coral reefs. (4) Not polluting the coastal environment. (5) Not catching protected fish and marine biota. (6) Not damaging/cutting down mangroves.